2021
DOI: 10.1152/ajplung.00511.2020
|View full text |Cite
|
Sign up to set email alerts
|

Adhatoda vasica rescues the hypoxia-dependent severe asthma symptoms and mitochondrial dysfunction

Abstract: Severe asthma is a chronic airway disease that exhibits poor response to conventional asthma therapies. Growing evidence suggests that elevated hypoxia increases the severity of asthmatic inflammation among patients and in model systems. In this study, we elucidate the therapeutic effects and mechanistic basis of Adhatoda Vasica (AV) aqueous extract on mouse models of acute allergic as well as severe asthma subtypes at physiological, histopathological, and molecular levels. Oral administration of AV extract at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…We have recently shown that AV alleviates the severe airway inflammation in steroid-nonresponsive asthmatic features by inhibition of HIF-1α (key transcription factor in hypoxia) via its negative regulator, PHD2. AV thereby modulates hypoxic response, which forms the basis for its diverse therapeutic effects including amelioration of mitochondrial dysfunction [16]. In this study we examined anti-hypoxic effects of AV in other hypoxia-inflammation prevalent conditions such as lung injury, fibrosis, and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that AV alleviates the severe airway inflammation in steroid-nonresponsive asthmatic features by inhibition of HIF-1α (key transcription factor in hypoxia) via its negative regulator, PHD2. AV thereby modulates hypoxic response, which forms the basis for its diverse therapeutic effects including amelioration of mitochondrial dysfunction [16]. In this study we examined anti-hypoxic effects of AV in other hypoxia-inflammation prevalent conditions such as lung injury, fibrosis, and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…For transcriptomic study, BALB/c mice were divided into Vehicle (distil water, oral, two times a day, n = 4) and Adhatoda Vasica (AV) extract group. AV group was further subdivided according to its dose: AV-D2 (Adhatoda Vasica extract 130 mg/kg, dissolved in distilled water, oral, two times a day, n = 5) and AV-D4 (Adhatoda Vasica extract 260 mg/kg, dissolved in distilled water, oral, two times a day, n = 5) as described previously [16]. Distil water or AV (130 mg/kg or 260 mg/kg) treatment was given to mice by oral gavage for four consecutive days, as represented in the Fig.…”
Section: Grouping and Treatment Of Micementioning
confidence: 99%
See 3 more Smart Citations